How I treat CML blast crisis - Hehlmann, Rüdiger (Blood, 2012)
Blast crisis (BC) remains the major challenge in the management of chronic myeloid leukemia (CML). It is now generally accepted that BC is the consequence of continued BCR-ABL activity leading to genetic instability, DNA damage, and impaired DNA repair. Most patients with BC carry multiple mutations, and up to 80% show additional chromosomal aberrations in a nonrandom pattern. Treatment with tyrosine kinase inhibitors has improved survival in BC modestly, but most long-term survivors are those who have been transplanted. Patients in BC should be treated with a tyrosine kinase inhibitor according to mutation profile, with or without chemotherapy, with the goal of achieving a second chronic phase and proceeding to allogeneic stem cell transplantation as quickly as possible. Although long-term remissions are rare, allogeneic stem cell transplantation provides the best chance of a cure in BC. Investigational agents are not likely to provide an alternative in the near future. In view of these limited options, prevention of BC by a rigorous and early elimination of BCR-ABL is recommended. Early response indicators should be used to select patients for alternative therapies and early transplantation. Every attempt should be made to reduce or eliminate BCR-ABL consistent with good patient care as far as possible.